Development of Chlorine Dioxide Releasing Film and Its Application in Decontaminating Fresh Produce. Issue 2 (7th January 2013) - Ray, Soumi; Jin, Tony; Fan, Xuetong; Liu, Linshu; Yam, Kit L.
Abstract A feasibility study was conducted to develop chlorine dioxide (ClO2)‐releasing packaging films for decontaminating fresh produce. Sodium chlorite and citric acid powder were incorporated into polylactic acid (PLA) polymer. Films made with different amounts of PLA (100 and 300 mg), percentages of reactant (5% to 60%), and ratios of sodium chlorite to citric acid (1:2 or 2:1) were prepared using a solvent casting method. The release of ClO2 from the resultant films was activated by moisture. Increase of reactants in the films produced more ClO2 while higher PLA content in the films resulted in less release of ClO2. The ratio of sodium chlorite to citric acid and activation temperature (22 °C compared with 10 °C) did not affect the ClO2 release from the films. Antimicrobial efficacy of ClO2 released from the films was evaluated using grape tomato as a model food. The results indicate that the films were activated by moisture from tomatoes in the package and the released ClO2 reduced Salmonella spp. and Escherichia coli O157:H7 inoculated on the tomatoes to undetectable levels (<5 colony forming units (CFU)/tomato), achieving more than 3 log reduction. The film‐treated tomatoes did not show significant changes in color and texture as compared to controls during storage at 10 °C for 21 d. This study demonstrated the technical feasibility for development of gaseous ClO2‐releasing packaging system to enhance microbial safety and extend shelf life of fresh produce.